Alternative assets : investments for a post-crisis world - Fraser-Sampson, Guy. (Hoboken, N.J. : Wiley, 2011)
This book will provide investors with a primer on each alternative asset class, plus practical tips on pros and cons, implementation, returns analysis, and fees and costs. It provides investors with a primer on each alternative asset class, as well as practical tips on the pros and cons, implementation, returns analysis, fees and costs. It also offers introductory guidance on how to set investment targets, and how alternative assets can be accommodated within the allocation process. Each chapter gives useful background knowledge on a particular asset type, including a discussion of whether a satisfactory beta return level exists and, if so, the different ways in which it might be accessed. Written by best-selling author Guy Fraser-Sampson, this book guides investors through the new look alternative investment arena, providing post-financial crisis perspective and investment advice on the alternatives landscape"--
Includes bibliographical references and index.
rua 26/04/13
Loans
Keywords: Portfolio management; Investment analysis; Finance